ELECTRONIC ASSESSMENT OF PROFESSIONAL ACTIVITIES OF PEDAGOGICAL STAFF IN GENERAL SECONDARY EDUCATION INSTITUTIONS: A COMPETENCY CONTEXT (Innovative professional education, 2024)
The competencies of educational staff in the aspect of electronic assessment of their professional activities in general education institutions are disclosed, which is key to enhancing the quality of the educational process. The research focuses on the analysis of information-digital competence, which enables educators to effectively use digital technologies in the educational process, evaluative-analytical competence, which aids in critical analysis and self-assessment, innovative competence, which stimulates the introduction of innovative approaches and methodologies, and reflective competence for continuous self-improvement and theability to learn throughout life, providing a foundation for teachers' adaptation to changes in the education sector. The findings underscore the importance of the electronic assessment of the professional activities of educational staff in general education institutions.
Keywords: electronic assessment, professional activity, educational staff, informational-digital competency, evaluative-analytical competency, innovative competency, reflective competency, lifelong learning ability